Maxillary Sinus Floor Augmentation to Enable One-Stage Implant Placement by Using Bovine Bone Substitute and Platelet-Rich Fibrin - Barbu, Horia Mihail (Biomed Res Int, 2018)
Nowadays it is possible to perform an optimal implant placement and to achieve a good long-term prognosis for an implant-borne prosthesis in the grafted posterior maxilla. This study evaluates the efficiency of one-stage piezosurgery by using as graft material a combination of particulate bovine bone substitutes with platelet-rich fibrin to achieve sinus lift. We included in this study 14 cases of one-stage sinus lift surgeries during which we placed 30 standard implants. The mean vertical bone height gain was 10.12 mm six months after surgery, and the mean postoperative follow-up time was 43.79 months. There were no major complications during or after surgery, and all implants are in use. Therefore, it can be concluded that one-stage sinus piezosurgery using particulate bovine bone substitutes and platelet-rich fibrin can be applied as a predictable and effective technique in the treatment of the posterior edentulous maxilla ensuring 4-5 mm vertical bone height.